Pelaksanaan Adopsi Anak dan Aspek Hukumnya (Studi di Panti Asuhan Panjura Kota Malang) - Chandra Andreas Cahyana (University of Merdeka Malang, 2022)
Children are one of the most beautiful gifts of Almighty God that is always coveted byevery married couple or family. Complete happiness in a family can be seen with thepresence of the baby as a complement and also to continue the offspring in the family. But not all families can have offspring that can eventually cause disharmony between husband and wife and in certain situations can lead to divorce. One solution that can be taken for families who do not have children is to adopt or raise a child, either the child of a relative / family or a child who is in an orphanage. The purpose of this study is to find out how the procedure for removing children at the Panjura Orphanage in Malang city. In addition, to find out what legal requirements must be met in the adoption of children at the Panjura Orphanage in Malang City.